Laporan kunjungan kerja Komisi IV DPR-RI reses masa persidangan ke IV tahun sidang 1988/1989 (Komisi IV, DPR-RI, 1989)
Forestry, transmigration, and agricultural affairs; report of a visit of the 4th Commission of Parliament.